HUBUNGAN KARAKTERISTIK MAHASISWA DAN LINGKUNGAN KLINIK DENGAN GEJALA STRES KERJA PADA MAHASISWA KLINIK PRODI KESEHATAN GIGI POLTEKKES KEMENKES KUPANG - Pinat, Leny Marlina A.; Merniwati Sherly Eluama; Christina Ngadilah (Program Studi Akuntansi IKOPIN, 2022)
This study aims to analyze the relationship between student characteristics and the clinical environment with symptoms of work stress in students of the Dental Health Study Program, Ministry of Health, Kupang Health Polytechnic. M This research is a cross sectional study, conducted on students in semester IV of the Dental Health Study Program. The number of samples was 86 people where the sampling procedure was carried out by total sampling technique. The data was taken through the interview method with a questionnaire containing questions to measure the characteristics of students, the clinical environment and symptoms of work stress. The results of the study were cross tabulated and analyzed statistically using the ANOVA test and persion correlation with a significance value of p <0.05. The results of this study indicate that the significance value is 0.111> 0.05, so it can be concluded that the average of the five student characteristics has no significant relationship with work stress, while there is a significant relationship between the clinical environment and symptoms of work stress with a significance of 0.003.